Pengaruh Pemanfaatan Abu Cangkang Kerang Darah sebagai Bahan Tambah Filler Campuran Aspal terhadap Nilai Marshall pada Perkerasan Jalan AC-WC - Sitompul, Obed Haposan; Alamsyah, Wan; Basrin, Defry (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Blood clam is a popular shellfish in Indonesia. Especially in Langsa because it is close to the sea area, blood cockles are found in large numbers which produce waste in the form of shells in large quantities. However, blood cockle shells contain calcium carbonate (CaCO3), which functions to bind water because water is the enemy of asphalt which can affect the age of asphalt, so the ash of blood cockle shells can be used as a filler. The aim of this test is to determine the stability and durability values due to the effect of adding blood cockle shell ash content as an additive to filler with blood cockle shell ash content of 0%, 30%, 50%, 70% and 100 %. The method used is the experimental method, namely experimental activities to obtain data. In this study, the addition of blood cockle shell ash as an added filler to the AC-WC asphalt mixture on the Marshall value showed that the greatest stability value was at 30 minutes of immersion, namely at a percentage of 50%, 1557.93 kg and the greatest stability value was at 8 hours of immersion, namely at a percentage of 50% it is 1404.40 kg. In this study, durability values were obtained based on the analysis results that at variations of 0%, 30% and 50% blood cockle shell ash content as a filler additive had the best durability values with values of 93.30%, 92.42% and 90.15% above 90% in accordance with the specifications required by the Department of Highways 2010. Key words : AC-WC, Blood clam shell ash, Marshall, Durability